Performance of plantar pressure measurement devices (PMDs): update on consensus activities - Claudia Giacomozzi (Istituto Superiore di Sanità, 2010)
A worldwide scientific discussion has been started in 2010 on the need for standardisation, assessment, and delivery of recommendations in the field of plantar pressure distribution measurement at different levels: hardware performance, measuring protocols, data processing, parameters and indicators in diagnosis and therapy. The Italian National Institute of Health (Istituto Superiore di Sanità, ISS) has been conducting for years a scientific project and several activities aimed to design, validate and implement dedicated testing methods and recommendations in the field of pressure measurement devices (PMDs). The present commentary contains a summary of the activities conducted up to now and some future steps which are going to be done at an international level.